2022
DOI: 10.1128/aac.01427-21
|View full text |Cite
|
Sign up to set email alerts
|

Population Pharmacokinetic Modeling of Total and Free Ceftriaxone in Critically Ill Children and Young Adults and Monte Carlo Simulations Support Twice Daily Dosing for Target Attainment

Abstract: Critical illness, including sepsis, causes significant pathophysiologic changes that alter the pharmacokinetics (PK) of antibiotics. Ceftriaxone is one of the most prescribed antibiotics in patients admitted to the pediatric intensive care unit (PICU). We sought to develop population PK models of both total ceftriaxone and free ceftriaxone in children admitted to a single-center PICU using a scavenged opportunistic sampling approach. We tested if the presence of sepsis and phase of illness (before or after 48 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(28 citation statements)
references
References 35 publications
(42 reference statements)
2
25
0
Order By: Relevance
“…Population pharmacokinetic (PPK), combined with a Monte Carlo simulation, provide feasible technical support for solving initial dosage recommendations in clinical practice. In recent years, more and more related research has been reported, which further verifies the reliability and practicability of this method (Jaruratanasirikul et al, 2019;Ren et al, 2019;Ghoneim et al, 2021;Rinaldi et al, 2021;Tang Girdwood et al, 2022). Hence, the present study recommends initial dosages of sirolimus in pediatric patients with PIK3CD mutationrelated immunodeficiency disease based on PPK and a Monte Carlo simulation.…”
Section: Introductionsupporting
confidence: 68%
“…Population pharmacokinetic (PPK), combined with a Monte Carlo simulation, provide feasible technical support for solving initial dosage recommendations in clinical practice. In recent years, more and more related research has been reported, which further verifies the reliability and practicability of this method (Jaruratanasirikul et al, 2019;Ren et al, 2019;Ghoneim et al, 2021;Rinaldi et al, 2021;Tang Girdwood et al, 2022). Hence, the present study recommends initial dosages of sirolimus in pediatric patients with PIK3CD mutationrelated immunodeficiency disease based on PPK and a Monte Carlo simulation.…”
Section: Introductionsupporting
confidence: 68%
“…From the viewpoint of pharmacokinetics/pharmacodynamics (PK/PD), beta-lactams increase clinical efficacy by increasing the frequency of administrations [ 16 ]. In fact, clinical studies reported the effectiveness of ceftriaxone twice daily [ 17 , 18 ]. Ceftriaxone exerts its bactericidal effect in a time-dependent manner, and the time spent above the MIC (%TAM) is an important PK/PD parameter for estimating clinical efficacy.…”
Section: Discussionmentioning
confidence: 99%
“…SIRS criteria are often met through presence of fever and tachycardia, especially in the setting of infection, in critically ill children. Our model of ceftriaxone in critically ill children also showed that fever increased ceftriaxone clearance ( Tang Girdwood et al, 2021 ). Fever is not a covariate that is frequently considered in the development of population PK models.…”
Section: Who Might Benefit From β-Lactam Precision Dosing?mentioning
confidence: 70%
“…Patients with higher antibiotic clearance are at risk of low exposures and suboptimal antibacterial efficacy. In Table 1 , we summarize several population PK models in critically ill children for ceftriaxone, piperacillin/tazobactam, cefepime and meropenem, the β-lactam antibiotics often used for sepsis in the pediatric ICU (PICU) ( Li et al, 2013 ; Cies et al, 2014a ; Nichols et al, 2016 ; Shoji et al, 2016 ; Cies et al, 2017 ; De Cock et al, 2017 ; Beranger et al, 2019 ; Al-Shaer et al, 2020b ; Hartman et al, 2021 ; Saito et al, 2021 ; Tang Girdwood et al, 2021 ; Yonwises et al, 2021 ; de Cacqueray et al, 2022 ). The one patient factor that consistently demonstrates an effect on clearance is estimated glomerular filtration, typically based on creatinine.…”
Section: Who Might Benefit From β-Lactam Precision Dosing?mentioning
confidence: 99%
See 1 more Smart Citation